Does Mergers and Acquisition Improve Performance? - Zhong, Zhuqiang (2013)
Merger and acquisition is an important way for companies to expand market share, obtain greater market power and set up new disciplines. Generally, people believe that merger and acquisition would bring benefit from the acquirer as the managers of acquirers are assumed make rational decisions. However, previous studies have shown that acquirers may not benefit from merger. Researchers conduct studies on merger performance from various prospective in order to explain the post merger performance of the target or acquirer. For example, some of them focus on the relationship between the payment method and merger performance. Some of them focus on the industry relevance while some may believe the initial share in target may affect post merger performance. In this dissertation, we are going to analysis the merger performance in a different way. We will use event study method to find out the relationship between the merger performance and the way of merger, takeover and tender offer.